EATING BEHAVIORS AMONG ADOLESCENT GIRLS: A SCOPING REVIEW - Fauni, Alimni Mayang; Shaluhiyah, Zahroh; Winarni, Sri (Media Gizi Indonesia, 2025)
Adolescent girls in developed and developing countries currently are prone to face malnutrition, both over- and under-nutrition. One of the causes is the shift from traditional to modern diets. This study aimed to determine the factors that influence the dietary behavior of adolescent girls in developed and developing countries. Scoping review performed following the PRISMA-ScR protocol with the Population, Exposure, and Outcome (PEO) approach. Described articles were published between 2014 and 2024, including abstracts and full texts from PubMed, Scopus, and Science Direct databases. The search used the keywords “eating habits*” OR “diet*” OR “dietary intake”, “adolescent girls*” OR “adolescent women*” OR “young women”. The results showed that diets of adolescent girls in both developed and developing countries correlated with malnutrition, characterized by high consumption of fast food that high in sodium and low in fiber. In developed countries, this resulted in obesity, while in developing countries it caused iron and calcium deficiencies. In developed countries, adolescent diets influenced by bullying and media pressure that idealizes thin bodies, thus triggered irregular eating patterns. Meanwhile, in developing countries, low family income, limited access to healthy food in school canteen, lack of time and cooking skills triggered low-nutrition diets. Parental support played an important role in increasing the consumption of healthy foods. Unhealthy diets increased the risk of anemia, obesity, malnutrition, and other eating disorders. Adolescent girls’ eating behavior influenced by nutritional, social, economic, lifestyle, and psychosocial factors.